Production of N-containing Chemicals and Materials from Biomass - Fang, Zhen.; Smith Jr, Richard Lee.; Xu, Lujiang (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book is a collection of studies on state-of-art techniques developed for producing value-added N-containing chemicals and N-doped carbon materials from renewable sources via sustainable technologies. Aiming to improve conversion effectiveness and develop innovative techniques for new value-added N-containing products, topics in the text address recent advances, assess and highlight promising methods or technological strategies, and outline direct conversion routes for conversion of renewable resources to N-containing chemicals and materials. World-renowned authorities, experts, and professionals have contributed individual chapters in selected areas to cover the overall topic comprehensively. In addition to researchers and professionals in the field, educators teaching university courses on biomass transformation, biomass energy, energy materials, heterocyclic chemistry, resource materials and sustainable development and green chemistry will find the text informative with new international perspectives. .
Chapter 1. Hydrolysis of nitrile compounds in near-critical water -- Chapter 2. Major advances in syntheses of biomass based amines and pyrrolidone products by reductive amination process of major bio-derived platform molecules -- Chapter 3. Producing N-heterocyclic compounds from lignocellulosic biomass feedstocks -- Chapter 4. Waste shell biorefinery: sustainable production of organonitrogen chemicals -- Chapter 5. Sustainable production of nitriles from biomass -- Chapter 6. Catalytic upgrading of bio-based ketonoc acids to pyrrolidones with hydrogen donor sources -- Chapter 7. Microbial production of amine chemicals from sustainable substrates -- Chapter 8. Engineering biochar-based materials for carbon dioxide adsorption and separation -- Chapter 9. Producing N-containing chemicals from biomass for high performance thermosets -- Chapter 10. Preparation of N-doped carbon materials from lignocellulosic biomass residues and their application to energy storage and conversion devices -- Chapter 11. Preparation of green N-doped biochar materials with biomass pyrolysis and their application to catalytic systems -- Chapter 12. Evaluating the role of gasification stages on evolution of fuel-N to deepen in sustainable production of NH3.
Keywords: Biotechnology; Refuse and refuse disposal; Environmental engineering; Bioremediation; Renewable energy sources; Biotechnology; Waste Management/Waste Technology; Chemical Bioengineering; Environmental Engineering/Biotechnology.; Renewable Energy